Halal food certification for improving the competitiveness of small and medium enterprises - Sylva Alif Rusmita, Tika Widiastuti, Ririn Tri Ratnasari, Sri Gunawan, Bayu Taufik Possumah,; Herianingrum, Sri (Opción, 2019)
The purpose of this study is to find out what factors influence and which factors play the most powerful role in influencing efforts to improve the competitiveness of Small and Medium Enterprises in Eastern Indonesia via a comparative qualitative research method. The results of this study found that there are several factors influencing efforts to improve the competitiveness of Eastern Indonesia Small and Medium Enterprises. In conclusion, the dominant factor is that policy and infrastructure want to illustrate the extent to which the implementation of policies and infrastructure in locations around MSMEs operate can support or hinder businesses to operate.